Articular Cartilage Inspired the Construction of LTi–DA–PVA Composite Structure with Excellent Surface Wettability and Low Friction Performance - Cui, Lingling; Chen, Junyue; Yan, Chengqi; Xiong, Dangsheng (Tribology letters, 2021)
On the purpose of improving the surface wettability and tribological properties of Ti6Al4V alloy for artificial joints, we designed a novel ‘soft (hydrogel layer)–hard (porous Ti6Al4V alloy substrate)’ structure, which was fabricated by laser texturing, surface dopamine modification and poly(vinyl alcohol) (PVA) hydrogel casting. Characterization results revealed that the PVA hydrogel layer could be attached to Ti6Al4V alloy successfully, and the LTi–DA–PVA specimen obtained a hydrophilic surface with a static water contact of 32°. It is worth noting that compared to the pristine Ti6Al4V alloy, the friction coefficient of the LTi–DA–PVA specimen could be as low as 0.01, which is similar to that of natural cartilage. This result was attributed to the synergistic effect of the high load-bearing capacity of the lower Ti6Al4V substrate and the good biphasic lubrication of the upper PVA hydrogel layer. In addition, the introduction of dopamine could significantly improve the interfacial bonding performance between the substrate and the hydrogel layer. This work provides an effective method for improving the surface wettability and tribological properties of Ti6Al4V as artificial joints.